Poly (ɛ-caprolactone) electrospun scaffolds filled with nanoparticles. Production and optimization according to Taguchi's methodology - Silva, C. S. R. (2014)
Polycaprolactone (PCL) scaffolds were produced by electrospinning. Polymeric solutions in a mix of dichloromethane (DCM) and dimethylformamide were electrospun to form fibers in the sub-micron range. Physical properties of the PCL solutions were characterized with respect to density, viscosity, conductivity and surface tension. Processing was optimized following Taguchi's methodology to select the set of processing parameters that resulted in producing fibers with the smallest diameters, minimum number of defects and with the narrowest distribution of fiber diameter. Morphology of electrospun fibers was qualitatively and quantitatively analyzed for the different sets of processing parameters. The optimum conditions found to electrospun PCL were used to process PCL solutions containing nanoparticles of hydroxyapatite (HA) or bioactive glass (BG). Bioactivity of nanocomposite electrospun membranes in simulated body fluid (SBF) was analyzed and biological response was tested by assessing proliferation and viability of MT3C3-E1 preosteoblasts cultured on PCL and its nanocomposite membranes.